SDN Security in 6G: Future Technologies and Research Challenges - Hirsi, Abdinasir; Audah, Lukman; Adeeb Salh; Mohammed A Alhartomi; Sahar, Nan Mad; Salman Ahmed (International Journal of Integrated Engineering, 2026)
Sixth-generation (6G) wireless communication is expected to be launched by 2030, introducing advanced technologies to meet the demands of ultralow, intelligent, and highly secure networks. Software-defined networks (SDN) play a crucial role in enhancing 6G security by offering architectural flexibility, centralized intelligence, and programmable defenses that address the unique challenges of next-generation connectivity. However, securing these emerging technologies requires novel adaptive security solutions. Reliability and ultralow latency are fundamental to 6G, where security mechanisms play a pivotal role in ensuring trust and resilience. In this study, we explore the role of SDN in 6G, its emerging applications, security threats, and key technologies that enhance SDN security in 6G environments. Based on the review, nearly 95% of existing studies primarily focus on the control and application layers of SDN in 6G, while the role of the data plane remains largely underexplored and insufficiently addressed. Finally, we outline critical security challenges and future research directions. To the best of our knowledge, this is the first study to comprehensively summarize the applications, security challenges, and research directions for SDN security in 6G technologies.